2015 Kansas Winter Annual Forage Variety Trial - J. D. Holman; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 16 winter annual forage varieties were tested for performance near Garden City, KS, at the Southwest Research-Extension Center in 2014-2015. Winter crops evaluated included wheat, triticale, and cereal rye.
Keywords: winter annual forage variety trial; Kansas; wheat; triticale; cereal rye